FAKTORISASI POLINOMIAL ALJABAR DENGAN MENGGUNAKAN METODE EUCLIDEAN DAN FAKTOR PERSEKUTUAN TERBESAR - Rora Oktafia; Sri Gemawati; Endang Lily (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses a factorization of algebraic polynomial of order n using theEuclidean method and the greatest common factor. The new polynomial is equivalentto the original polynomial. The new polynomial is formed by multiplication of the rootsof the original polynomial.